Canopy structure and morphogenesis of italian ryegrass intercropped with red clover under cutting intervals determined by thermal sum - Ongaratto, Fernando [UNESP]; da Rocha, Marta Gomes; Pötter, Luciana; Bergoli, Tuani Lopes; Severo, Paula de Oliveira; Dutra, Juliana Squizani; Machado, Juliana Missio; Dotto, Lisiani Rorato; Martini, Amanda Carneiro; de Oliveira, Eduarda Proença (My University, 2020)
The canopy structure and morphogenesis of ryegrass (Lolium multiflorum Lam.) was investigated after it was over seeded with Tifton 85 (Cynodon spp.) and intercropped with red clover (Trifolium pratense L.). Time intervals between cuts were determined by different thermal sums (125, 250, 375, and 500 degree-days [DD]). Cuts were conducted at a height equivalent to 50% of the average canopy height. Morphogenic and structural data were collected from July to October of 2016 and 2017, from a completely randomized block experimental design. Canopy height, extended tiller height, pseudostem length, and forage mass were fitted to linear equations according to the thermal sums. Interaction of ryegrass with red clover was the highest (12.1%) for longer cut intervals (375 and 500 DD). The leaf appearance rate (0.0080 leaf/DD), phyllochron value (128.8 DD), and senescence rate (0.10 cm/DD) of ryegrass were comparable between the different intervals. The slowest elongation rate (0.06 cm/DD) with the shortest interval duration between cuts (171.6 DD) was observed in the 125 DD interval. According to the findings from this 2-year experiment, the use of a 250 DD cut interval was recommended between grazing events, taking into account the efficiency of forage use, ryegrass leaf, stem ratio, and interactions with red clover in the canopy under rotational stocking.
Estrutura do dossel e morfogênese do azevém anual consorciado com trevo vermelho em intervalos de corte determinados por soma térmica
Keywords: Lolium multiflorum Lam; Overseeding; Rotational Stocking; Tifton 85; Trifolium pratense L